Government Regulation, Executive Overconfidence, and Carbon Information Disclosure: Evidence From China - He, Ren; Cheng, Yanduo; Zhou, Mingdian; Liu, Jing; Yang, Qing (Frontiers in Psychology, 2021)
Climate change has put countries around the world under great pressure to reduce emissions. Chinese government has proposed that China will strive to peak carbon dioxide emissions before 2030 and achieve carbon neutrality before 2060. A low-carbon lifestyle is becoming a new trend in China. Therefore, the products of firms that actively respond to climate change are more popular for consumers in China. In the internet era, the carbon information disclosed by firms has become an important way for consumers to understand the behavior of firms in responding to climate change. In the existing literature on the influencing factors of carbon information disclosure, the psychological factors of executives are seldom investigated. Using a sample of Chinese listed firms in low-carbon pilot provinces and cities during the period of 2015-2019, this paper explores the influence of government regulation and executive overconfidence on the quality of carbon information disclosure. The results show that government regulation have a significantly positive effect on the quality of carbon information disclosure. The results also reveal that executive overconfidence negatively affects the quality of carbon information disclosure. Moreover, executive overconfidence negatively moderates the relationship between government regulation and the quality of carbon information disclosure. Our findings make a significant contribution to the role of executive’s psychological factors on firms behaviors and provide new insights and policy implications for government, firms, consumers and other stakeholders.